Evidence for reversible light-dependent transitions in the photosynthetic pigments of diatoms. Issue 49 (3rd November 2022) - Tselios, Charalampos; Varotsis, Constantinos
Abstract : A reversible light-intensity behavior of Dds and Fxs composition in the cells of T. pseudonana . The observed LL to HL reversible transitions are accompanied by structural modifications of Chls a / c and the lack of the red-shifted Fxs. Abstract : Marine diatoms contribute to oxygenic photosynthesis and carbon fixation and handle large changes under variable light intensity on a regular basis. The unique light-harvesting apparatus of diatoms are the fucoxanthin–chlorophyll a / c -binding proteins (FCPs). Here, we show the enhancement of chlorophyll a / c (Chl a / c ), fucoxanthin (Fx), and diadinoxanthin (Dd) marker bands in the Raman spectra of the centric diatom T. pseudonana, which allows distinction of the pigment content in the cells grown under low- (LL) and high-light (HL) intensity at room temperature. Reversible LL–HL dependent conformations of Chl c, characteristic of two conformations of the porphyrin macrocycle, and the presence of five- and six-coordinated Chl a / c with weak axial ligands are observed in the Raman data. Under HL the energy transfer from Chl c to Chl a is reduced and that from the red-shifted Fxs is minimal. Therefore, Chl c and the blue-shifted Fxs are the only contributors to the energy transfer pathways under HL and the blue- to red-shifted Fxs energy transfer pathway characteristic of the LL is inactive. The results indicate that T. pseudonana can redirect its function from light harvesting to energy-quenching state, and reversibly to light-harvesting upon subsequent illumination to LL by reproducing the red-shifted Fxs and decrease the number of Dds. The LL to HL reversible transitions are accompanied by structural modifications of Chl a / c and the lack of the red-shifted Fxs.